An analysis of urban form as an approach to social sustainability: a comparative study of contrasting housing developments - Botha, Deirdre (Department of Environmental and Geographical Science, 2019)
This research study aims to determine the impact of urban form on social sustainability. Definitions of urban form vary in the literature. One of the definitions describe urban form as spaces that enhance the sense of community, healthy communities and place attachment, while promoting environmental mitigation and adaption measures (Eizenberg & Jabareen, 2017). Likewise, social sustainability has not been clearly defined and universally understood and as a result its importance has been compromised (Vallance, Perkins & Dixon, 2011). This study of urban form also includes testing the success of the process of implementation, with the aim of providing evidence with regards to its success in the shaping of urban form. Important implementation processes of urban form include: planning processes, policies, processes of collaboration and partnership between different agencies, local participation, financial incentives, tax incentives and investment (Burton, Jenks & Williams, 2003). The case study of the research includes two contrasting housing developments that are at opposite ends of the housing spectrum. Masiphumelele, an informal settlement, and Lake Michelle, an Eco-Estate. Both these housing developments are situated between the areas of Noordhoek, Fish Hoek and Sun Valley in the City of Cape Town. This research project makes use of a multidisciplinary approach. Due to the spatial and social nature of the research, methods from both Geography and Urban Design were used. Qualitative methods were used, including interviews, field observation, volunteer work at an NGO, and spatial mapping. The research study finds that urban form does have an impact on social sustainability. The findings reveal that the measure of social sustainability is a result of firstly, the type of urban form. Secondly, it is a result of the nature of the implementation process of urban form. Third, it is a result of the residents’ response to the urban form. Social sustainability is thus not predictable, but the relationship between urban form and social sustainability is predictable. Both high-density and low-density urban forms have positive and negative results, depending on the specific context. Furthermore, the selected criteria with which to define both urban form and social sustainability will have an impact on the relationship between the two. Thus, calling for a uniform definition of both urban form and social sustainability, and the need for a context-specific approach to the design of urban form.